Epidemiology and outcome of adult out-of-hospital cardiac arrest of non-cardiac origin in Osaka: a population-based study. Issue 12 (22nd December 2014) - Kitamura, Tetsuhisa; Kiyohara, Kosuke; Sakai, Tomohiko; Iwami, Taku; Nishiyama, Chika; Kajino, Kentaro; Nishiuchi, Tatsuya; Hayashi, Yasuyuki; Katayama, Yusuke; Yoshiya, Kazuhisa; Shimazu, Takeshi
Abstract : Objectives: To evaluate epidemiological characteristics of out-of-hospital cardiac arrests (OHCAs) by detailed non-cardiac cause and factors associated with the outcomes after OHCAs of non-cardiac origin. Design: A prospective, population-based observational study. Setting: The Utstein Osaka Project. Participants: 14 164 adult patients aged ≥20 years old with OHCAs due to non-cardiac origin who were resuscitated by emergency-medical-service personnel or bystanders, and then were transported to medical institutions from January 2005 to December 2011. Primary outcome measures: One-month survival after OHCA. Multiple logistic regression analysis was used to assess factors that were potentially associated with the outcome. Results: During the study period, the 1-month survival rate was 5.3% (755/14 164). The proportion of 1-month survival was 6.2% (510/8239) in external causes, 6.5% (94/1148) in respiratory diseases, 0.8% (11/1309) in malignant tumours, 4.9% (55/1114) in strokes and 4.1% (85/2054) in others. As for external causes, the proportion of 1-month survival was 14.3% (382/2670) in asphyxia, 4.2% (84/1999) in hanging, 0.7% (9/1300) in fall, 1.1% (12/1062) in drowning, 1.6% (12/765) in traffic injury, 3.7% (7/187) in drug overuse and 1.6% (4/256) in unclassified external causes. In a multivariate analysis, adults aged <65 years old with arrests witnessed by bystanders, with normal activities of daily living before the arrests, having ventricular fibrillation arrests, having arrests in public places, intravenous fluid levels and early Emergency Medical Service response time were significant predictors for 1-month outcome after OHCAs of non-cardiac origin. The proportion of 1-month survival of all OHCAs of non-cardiac origin did not significantly increase (from 4.3% (86/2023) in 2005 to 4.9% (105/2126) in 2011) and the adjusted OR for one-increment of year was 1.01 (95% CI 0.97 to 1.06). Conclusions: From a large OHCA registry in Osaka, we demonstrated that 1-month survival after OHCAs of non-cardiac origin was poor and stable.